THU0156 Clinical assessment versus ultrasonography in patients with rheumatoid arthritis treated with biological agents - the impact of concomitant fibromyalgia. (15th June 2017) - Tamas, MM; Ghib, L-J; Bondor, CI; Felea, I; Damian, L; Filipescu, I; Mociran, A; Simon, S-P; Muntean, L; Rednic, S
Abstract : Background: Concomitant fibromyalgia (FM) may increase subjective components of the disease activity scores (DAS) in rheumatoid arthritis (RA), thus leading to an improper assessment of treatment response. Ultrasonography (US) is currently used in clinical practice as an objective measure of the disease activity. The US7 German score was demonstrated to be sensitive to change, reflecting the therapeutic response in RA patients [1]. Objectives: To evaluate clinical and US parameters in RA patients with or without concomitant FM, undergoing biological therapy. Methods: RA patients treated with various biological agents who presented in our Department of Rheumatology were consecutively enrolled. Patients underwent clinical and laboratory examinations. US was performed by an experienced sonographer, blinded to clinical evaluation. Synovitis and synovial/tenosynovial vascularity were scored semiquantitatively (grade 0–3) by gray-scale (GS) and power Doppler (PD) US. Tenosynovitis (TS) and erosions were scored for presence [1]. Patients were divided in two groups according to the difference between tender joint count (TJC) and swollen joint count (SJC): ≥7 RA-FM group, <7 RA-nonFM group, representing the "joint count" criteria for FM, after the study of Pollard et al . [2]. Results: Thirty-nine patients were included, 77% women, mean age 55.2±11.3 years, mean disease duration 15.25±9.4 years. Nine out of 39 (23%) patients were classified as having associated FM. Disease duration and treatment were comparable between groups. Significantly higher values for TJC, patient global assessment (PGA), DAS 28 were found in the RA-FM group, with no differences for SJC or inflammatory markers (ESR, CRP). GS and PD-US7 scores were similar between groups (Table 1 ). In the RA non-FM, but not in the RA-FM group, GS and PD-US7 correlated with SJC (r=0.44, p =0.015 – GS synovitis, r=0.47, p =0.008 – PD synovitis; r=0.57, p =0.001 – GS TS; r=0.46, p =0.011 – PD TS) and PD synovitis negatively correlated with the "joint count" criteria (r=-0.44, p =0.015). Conclusions: Concomitant FM in RA patients undergoing biological therapy lead to higher DAS28 scores, but not to synovial inflammation on US. US-PD correlates with clinically detected synovitis in the non-FM group. US is expected to modify treatment decision and to prevent RA mistreatment especially in RA-FM patients. References: Backhaus M, et al. Evaluation of a novel 7-joint ultrasound score in daily rheumatologic practice: a pilot project. Arthritis Rheum. 2009;61(9):1194–201. Pollard LC, et al. Fibromyalgic rheumatoid arthritis and disease assessment. Rheumatology (Oxford). 2010;49(5):924–928. Disclosure of Interest: None declared